PREVALENCE, PATTERN, AND DETERMINANT OF SEX PREFERENCE IN INDIA: EVIDENCE FROM INDIA HUMAN DEVELOPMENT SURVEY-II (2011-12) - Dakua, Manoj; Sarkar, Bappa (International Journal of Research -GRANTHAALAYAH, 2021)
Sex preference is highly dominated in India and its adjacent South Asian countries. The present study examines the pattern, prevalence, and determinants of sex preference for an extra child at India’s national and regional levels. For this study, we have utilized the secondary data of the Indian Human Development Survey-II. Bivariate analysis and multivariate logistic regression analysis were carried out to understand the difference of sex preference for an extra child by selected background variable- prevalence of sex preference almost 40% in India. Sex preference is higher among women who have three alive children, where the son’s preference is more who have at least four living children. Son preference is decreasing with the increase of women’s educational levels. On the contrary, sex preference is more among lower age at marriage. The odds of sex preference are higher among those above bachelor’s degrees than those with no formal education. On the contrary, sons’ preference is higher who completed their primary education than those who have no education. Sex preference, especially son’s preference, directly or indirectly affects on sex ratio. Therefore, Government should focus on an awareness program and make some policies for a venerable woman identified in this study.